The Role of Transient Receptor Potential A1 and G Protein-Coupled Receptor 39 in Zinc-Mediated Acute and Chronic Itch in Mice - Hu, Yue; Fu, Qing-Yue; Fu, Dan-Ni; Wang, Xue-Long; Wang, Zhi-Hong; Zhang, Jiang-Tao; Xu, Wen-Jing; Zhou, Guo-Kun; Chen, Li-Hua; Liu, Tong (Frontiers in Molecular Neuroscience, 2022)
Itch is a common symptom of many skin or systemic diseases and has a negative impact on the quality of life. Zinc, one of the most important trace elements in the organism, plays an important role in the regulation of pain. Whether and how zinc regulates itch is largely unclear. Herein, we explored the role of Zn2+ in regulation of acute and chronic itch in mice. It is found that intradermal injection of Zn2+ dose-dependently induced acute itch and TRPA1 participated in Zn2+-induced acute itch in mice. Moreover, pharmacological analysis showed the involvement of histamine, mast cells, opioid receptors, and capsaicin-sensitive C-fibers in Zn2+-induced acute itch in mice. Systemic administration of Zn2+ chelators such as TPEN (N,N,N′,N′-Tetrakis(2-pyridylmethyl)ethylenediamine), pyrithione, and clioquinol were able to attenuate both acute itch and dry skin-induced chronic itch in mice. Q-PCR analysis showed the mRNA expression levels of zinc transporters (ZIPs and ZnTs) significantly changed in the dorsal root ganglia (DRGs) under dry skin-induced chronic itch condition in mice. Activation of ERK pathway was induced in the DRG and skin by administration of zinc or under dry skin condition, which was inhibited by systemic administration of Zn2+ chelators. Finally, we found that the expression of GPR39 (a zinc-sensing GPCR) was significantly up-regulated in the dry skin mice model and involved in the pathogenesis of chronic itch. Together, these results indicated that the TRPA1/GPR39/ERK axis mediated zinc-induced itch, and thus targeting zinc signaling may be a promising strategy for anti-itch therapy.